2018
DOI: 10.1039/c8cp02144a
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the binding site between bovine serum albumin and ultrasmall SiC fluorescent biomarkers

Abstract: Ultrasmall silicon carbide nanoparticles (SiC USNPs) are very promising biomarkers for developing new applications in diagnostics, cell monitoring or drug delivery, even though their interaction with biological molecules such as different proteins has not yet been investigated in detail. In this study, the biological behaviour of SiC USNPs in a medium modeling a living organism was investigated in detail through the dependence of the fluorescence on interactions between bovine serum albumin (BSA) and SiC USNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 87 publications
(98 reference statements)
0
10
0
Order By: Relevance
“…This protein has 76% sequence homology with human serum albumin (HAS), and it is one of the most studied proteins. 26 Particle Size and Morphology. The average hydrodynamic diameter and zeta-potential for the nanocarrier systems are reported in Figure 4A−C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein has 76% sequence homology with human serum albumin (HAS), and it is one of the most studied proteins. 26 Particle Size and Morphology. The average hydrodynamic diameter and zeta-potential for the nanocarrier systems are reported in Figure 4A−C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…23,24 In addition, the availability of sterilization via an industrial steam pressure sterilizer, lyophilization, and mass production make niosomes quite appropriate as ODN delivery systems. 25,26 Our research group has successfully synthesized BSA-coated niosomes (NISM@B) by a thin-film hydration method and characterized the system. 21 Obtained results showed that NISM@B has strong therapeutic agent binding capacity, low cytotoxicity, and high uptake efficiency.…”
Section: ■ Introductionmentioning
confidence: 96%
“…The positions of the A 1 -band, β-sheet and α-helix, T and A 2 -band of the amide-I (1600-1700 cm À1 ) of pure BSA were shifted from 1607 to 1620 cm À1 , 1629 to 1642 cm À1 , 1651 to 1655 cm À1 , 1668 to 1665 cm À1 , and 1689 to 1694 cm À1 , respectively. [62][63][64] The amide-A and amide-B of BSA shifted from 3245 to 3220 cm À1 and 3385 to 3381 cm À1 , respectively. [65] The peak shifting and shape change in the amide-I band, and the amide-A, B band is the signature for the unfolding of BSA due to the interaction with ZnO NRs.…”
Section: Ftir Spectroscopy Of Bsa-zno Nrs Bioconjugatementioning
confidence: 99%
“…Serum albumin is the most important protein in the blood serum, it has many functions such as keeping normal osmotic pressure, carrier of hormones, fatty acids, as well as metabolic function biotransformation (drug delivery media) of chemotherapeutic agents. [ 80,81 ] Therefore, the binding study of serum albumin is a very interesting area in pharmaceutical and biochemical applications. BSA is the most studied protein as it has about 76% similarity with human serum albumin HAS with respect to binding with bioactive compounds.…”
Section: Biological Applicationsmentioning
confidence: 99%